Retaining e-learners: A case study of e-PJJ program Universiti Teknologi MARA, Shah Alam Main Campus / Lenora Jailan Zainal - Jailan Zainal, Lenora (Faculty of Computer and Mathematical Sciences, 2007)
In this era of science and technology where the world seems to have no boundaries, the term e-learning has brought a new significance to education. Defined as acquisition and use of knowledge distributed and facilitated primarily by electronic means, Malaysia does not want to be left behind with this emergence of new technology. University Teknologi MARA is one of the universities in Malaysia who has been practicing this new learning method. However, even though this new means of delivering education has been getting good responds, there still exist problems which lead to a high number of students' attritions. This research seeks to determine what are the factors of attrition and also retention among students of e-PJJ. A research model has developed to conduct the research. A total of 200 questionnaires have been distributed among targeted respondents which are the current and former e-PJJ students who have dropped out. A total of 157 answered questionnaires have been retrieved back. An exploratory factor analysis has been run in analyzing the data in order to seek what are the most significant factors of attrition or retention. After the exploratory factor analysis has been run through the data, it is found out that the most significant factors of attrition or retention are individual background, academic integration and social integration. Thus, the objectives have been achieved. Recommendations have been provided as proposed means solutions to alleviate the problems.